Using metal alloys for dehalogenation of antibacterial agents triclosan, chlorophene and dichlorophene - Kamenická, Barbora; Pérko, Jan; Weidlich, Tomáš (Slovenská spoločnosť chemického inžinierstva, 2017)
Triclosan, chlorophene and dichlorophene are chlorinated phenols used as antimicrobial agents. Triclosan (5-chloro-2,4-dichlorophenoxy)phenol, TCS) was before restriction from European Union found in cosmetics, toothpastes, antibacterial soaps, and also can be found as an antibacterial preservative in plastics like kitchenware, toys as well in textile products like socks, bedings, sports clothing. Chlorophene (2-benzyl-4-chlorophenol, CLP) usage is similar to that with TCS in personal care products, household products but it is also used in the industry and agriculture (farming environments) as an active agent in disinfectants. Dichlorophene (2,2'-methylenebis(4-chlorophenol), DCP) is also used as TCS and CLP in household products a cosmetics and is also used in veterinary as an anticestodal agent – for the removal of parasites such as tapeworms from cats and dogs. All mentioned chlorinated antimicrobial agents are ordinarily detected in aquatic environments. The aim of this study is to show the applicability of different metallic alloys such as Al-Ni (50% Al, 50% Ni), Devarda´s alloy (45% Al, 50% Cu, 5% Zn), Arnd´s alloy (60% Cu, 40% Mg) for dehalogenation of mentioned chlorinated phenols in aqueous alkaline solution at ambient temperature and investigating such parameters as amount of alloy(s), type and amount of base, reaction time etc. Above mentioned alloys were used in the past studies for dehalogenation of several halogenanilines, 2,4,6-tribromophenol and were suggested as suitable reduction agents for halogenated phenols.
Možnosti použití kovových slitin pro dehalogenaci antibakteriálních prostředků Triclosanu, Chlorofenu a Dichlorofenu
Keywords: chlorophenol; hydrodechlorination; dechlorination; chlorfenol; hydrodechlorace; dechlorace